Experimental study of in-plane poled piezoelectric diaphragm-based MEMS devices - Shen, Zhiyuan. (2013)
In recent years, piezoelectric diaphragms with an in-planed poling scheme have been studied and have demonstrated improved actuation over traditional diaphragms. In this study, the design, fabrication and characterization of an in-plane poled MEMS piezoelectric diaphragm will be investigated, with the aim of demonstrating the diaphragm’s effectiveness in sensitivity improvement and its applications as an acoustic transducer and energy harvester.